Degradation performance analysis and operation optimization of rotary-traveling wave oscillators for RF-CMOS applications. (April 2021) - Sanabria Díaz, Carlos Alberto; Linares Aranda, Mónico; De la Hidalga Wade, Francisco Javier; Hernández Martínez, Luis
Abstract: In this work, the impact of the parasitic effects caused by discontinuities on Resonant Rotary Traveling Wave Oscillators (RTWO) for RF-CMOS applications, is analyzed and modeled. By using experimental data in addition to the full wave representation, semi-empirical models are obtained for different discontinuities contained in an RTWO. Then, using the proposed models and 180 nm CMOS process parameters, an RTWO was designed with an operating frequency of 20 GHz, whilst the impact of the discontinuities was quantified in its output signal. The results show that the impact of the parasitic elements due to these discontinuities present a filtering effect leading to a distortion of the magnitude and number of harmonics in the output signal, with a reduction of 13.8% when the effects of the geometrical discontinuities were included. In order to mitigate the parasitic effects due to discontinuities, the use of topological (layout) methods in stack paths and the Möbius connection are proposed. Additionally, a process variation analysis was conducted and the results show that the operation frequency could vary in a range from 17.21 GHz to 18.91 GHz; while the output voltage could fluctuate between 1.17 V and 1.91 V depending on the process, bias voltage and temperature (PVT) conditions. These effects must be taken into account in the design of RTWOs to avoid inefficient tuning stages, especially for high frequency applications, and for advanced technologies where the impact of the analyzed discontinuities is increased. Graphical abstract: Image 1 Highlights: Rotary traveling wave oscillator for RF applications. On-chip via stacks modeling for high frequency. S-parameters extraction in CMOS process. PVT analysis for RF oscillators.